Assessing nutrient limitation in complex forested ecosystems: alternatives to large‐scale fertilization experiments. Issue 3 (1st March 2014) - Sullivan, Benjamin W.; Alvarez-Clare, Silvia; Castle, Sarah C.; Porder, Stephen; Reed, Sasha C.; Schreeg, Laura; Townsend, Alan R.; Cleveland, Cory C.
Abstract : Quantifying nutrient limitation of primary productivity is a fundamental task of terrestrial ecosystem ecology, but in a high carbon dioxide environment it is even more critical that we understand potential nutrient constraints on plant growth. Ecologists often manipulate nutrients with fertilizer to assess nutrient limitation, yet for a variety of reasons, nutrient fertilization experiments are either impractical or incapable of resolving ecosystem responses to some global changes. The challenges of conducting large, in situ fertilization experiments are magnified in forests, especially the high‐diversity forests common throughout the lowland tropics. A number of methods, including fertilization experiments, could be seen as tools in a toolbox that ecologists may use to attempt to assess nutrient limitation, but there has been no compilation or synthetic discussion of those methods in the literature. Here, we group these methods into one of three categories (indicators of soil nutrient supply, organismal indicators of nutrient limitation, and lab‐based experiments and nutrient depletions), and discuss some of the strengths and limitations of each. Next, using a case study, we compare nutrient limitation assessed using these methods to results obtained using large‐scale fertilizations across the Hawaiian Archipelago. We then explore the application of these methods in high‐diversity tropical forests. In the end, we suggest that, although no single method is likely to predict nutrient limitation in all ecosystems and at all scales, by simultaneously utilizing a number of the methods we describe, investigators may begin to understand nutrient limitation in complex and diverse ecosystems such as tropical forests. In combination, these methods represent our best hope for understanding nutrient constraints on the global carbon cycle, especially in tropical forest ecosystems.